STUDI PENDAHULUAN DERIVATISASI BEBERAPA SENYAWA DENGAN GUGUS AMIN MENGGUNAKAN DANSIL KLORIDA PADA KLT-SPEKTROFOTODENSITOMETER - Apsari, Dewi Puspita; Laksmiani, Ni Putu Linda; Widjaja, I.N.K. (Jurnal Farmasi Udayana, 2013)
Advance derivatization study of several amines with dansyl chloride has been carried out. The aim of this study was to determine influence of molecul structures compound toward dansylation. Derivatization was done by reacting  4000 ng drugs which contain primary or secondary amine group with 100 ng dansyl chloride at a temperature 450 C and pH 9 for a hour. Interference was separated using stationary phase silica G60 and mobile phase  etyl acetat : methanol : ammonia (85:10:5), detection on spectrophotodensytometer ?eks 312 nm mode fluorescence with filter K400. Compounds that have a primary or secondary amine groups can be derivatized using  dansyl chloride though that most affects  of  the reaction is  rigidity of molecul structure. Differences fluorescence intensity between each derivatives influenced by the reactivity amine groups and steric hindrance of the compound.
Keywords: amine group, dansyl chlorida, derivatization, molecul structures, TLC-spectrophotodensytometer